2018
DOI: 10.1371/journal.pone.0203444
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of pollen nutrition on honey bee queen egg laying with a new laboratory system

Abstract: Honey bee populations have been declining precipitously over the past decade, and multiple causative factors have been identified. Recent research indicates that these frequently co-occurring stressors interact, often in unpredictable ways, therefore it has become important to develop robust methods to assess their effects both in isolation and in combination. Most such efforts focus on honey bee workers, but the state of a colony also depends on the health and productivity of its queen. However, it is much mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 78 publications
(86 reference statements)
3
36
0
Order By: Relevance
“…Low sample sizes in the preference tests of individual queen pairs also limited their statistical power but behavioral studies are very time consuming without automation of the assays. Likewise, the test of immune priming was plagued by low sample size; studies of mortality dynamics require much higher sample sizes and replicates distributed across many replicates because of the intrinsic stochasticity of mortality, particularly in laboratory cage studies [101,102]. Finally, the sampling schedule for collecting offspring may also have prevented us from finding an effect because immune priming can be transient [103] and offspring should have been tested at multiple time points after queen inoculation with IAPV.…”
Section: Discussionmentioning
confidence: 99%
“…Low sample sizes in the preference tests of individual queen pairs also limited their statistical power but behavioral studies are very time consuming without automation of the assays. Likewise, the test of immune priming was plagued by low sample size; studies of mortality dynamics require much higher sample sizes and replicates distributed across many replicates because of the intrinsic stochasticity of mortality, particularly in laboratory cage studies [101,102]. Finally, the sampling schedule for collecting offspring may also have prevented us from finding an effect because immune priming can be transient [103] and offspring should have been tested at multiple time points after queen inoculation with IAPV.…”
Section: Discussionmentioning
confidence: 99%
“…The full egg collection capacity of FECS estimated during the spring season (120-180 eggs/2 h), which was almost identical to the intrinsic egg laying capacity of a queen bee, is much larger than the currently reported egg collection efficiency (i.e., 62 eggs/2 h) that was estimated during the fall season. Therefore, the collection efficiency of FECS is likely more dependent upon the egg laying capacity of a queen bee, which changes due to various factors, including seasonal temperature fluctuation, worker bee number, and available food resource (Dunham 1930;Fine et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As the transparent nature of the film enables real-time observation of egg laying from the backside of the comb box, researchers can easily record or mark eggs, thereby allowing collection of a large quantity of eggs with known ages. The queen-monitoring cage (QMC) recently reported by Fine et al (2018) showed that 3D printed artificial comb can be used to monitor egg laying activity of the queen bee and they used the device to evaluate the effect of pollen nutrition on egg laying (Fine et al 2018). Although both FECS and QMC share several common features, QMC is more specialized for monitoring of egg laying under controlled laboratory system whereas FECS is more specialized for mass egg collection from field colonies.…”
Section: Discussionmentioning
confidence: 99%
“…The state of honeybee colonies depends on the queen's reproductive and health. Thus, the activity of queen, health, and physiological conditions of worker bees can affect the colony through protein nutrition "pollen" (Fine et al 2018). Jatropha seeds content about 33% protein, rich in various macro-elements and micro-elements as Mn, Fe, K, Mg, P, and Na (Abou-Arab and Abu-Salem, 2010).…”
Section: Biological Activities Of Treated Colonies Area Of Reared Broodmentioning
confidence: 99%